MADRASAH SEBAGAI ALTERNATIF PELAKSANAAN PENDIDIKAN ISLAM DALAM PERSEPSI MASYARAKAT - Wina Khaerunisa, Amirudin, Iqbal Amar Muzaki, Moh. Subhan (Universitas Islam Madura, 2021)
Islam places education as the main agenda in improving people's conditions, public awareness of education is also one of the backgrounds, year after year Islamic education in Indonesia has been recognized by the community so that many educational institutions have been established, both starting from the city area. From large to small areas such as villages, people are already aware of the importance of education, especially as humans who are Muslim, therefore it is obligatory to study Islamic teachings that have been conveyed by the Prophet Muhammad. Islam is an alternative to taking Islamic education by studying various kinds of Islamic teachings, of course. In this study, the researcher wants to discuss how the public view of madrasas as an alternative to Islamic education that has been implemented in many areas. This research is descriptive with a qualitative approach. then data collection data collection in this study was carried out through interviews, observations or observations and documents that had been given permission by the madrasa in question.